OPTIMIZING LEARNING ACHIEVEMENT IN FLOOR EXERCISES: A CASE OF ELEMENTARY SCHOOL IMPLEMENTATION WITH INCLINED PLANE MAT MEDIA - Muhiri Muhiri; Rahmat Sanusi; Hari Adi Rahmad; Karunia Yulinda Khairiyah; Samsuar Samsuar (LLDIKTI Wilayah X, 2023)
The purpose of this study was to improve the learning outcomes of front roll in class IV students of SDN 002 Karimun based on the results of observations that illustrate the low value of student completeness in learning floor gymnastics (front roll). This research is a Classroom Action Research (PTK) consisting of two cycles, with each cycle consisting of planning, action implementation, observation, and reflection. Data sources include student activity during learning, student knowledge tests regarding learning implementation, and floor gymnastics practice tests (front rollers). The data analysis technique uses descriptive percentages to reveal the results of classical learning completeness of class IV students of SD Negeri 002 Karimun in the 2020/2021 academic year. The results of this study indicate that the use of inclined plane mat media can improve the learning outcomes of floor gymnastics (front rollers) in class IV students of SD Negeri 002 Karimun. The learning results of floor gymnastics (front rollers) in Cycle I obtained a result of 60%. In cycle II there was an increase in student learning outcomes of floor gymnastics (front rollers) by 100%. The results of the study can conclude that the inclined plane tool can improve the learning outcomes of floor gymnastics (front rollers) in class IV students of 002 Karimun State Elementary School.